Edukasi Kehamilan dan Persalinan yang Aman dengan Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) - Fikria Nur Ramadani; Shanti Ariandini; Nadhita Denia Putri; Putri Rinjani M (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Maternal Mortality Rate (MMR) is one of the indicators of the quality of maternal and child health services in a country. Based on data from the 2024 SDKI (Indonesia Demographic and Health Survey), the maternal mortality rate decreased compared to the previous year, from 4,482 cases in 2023 to 4,150 deaths in 2024, but this figure is still far from the 2030 SDG target. In an effort to reduce maternal mortality, the government's program is the Program for Birth Planning and Complication Prevention (BPCR or P4K in bahasa), which emphasizes community empowerment in monitoring pregnant, delivering, and postpartum mothers. In its implementation, P4K still faces obstacles, one of which is the lack of knowledge among mothers and the community regarding P4K. This also occurs in RW17, Cilendek Barat Village, where many people are still unaware of P4K. Health education interventions about the importance of P4K are one of the activities carried out to increase the knowledge of mothers and the community. Participants are pregnant women, community health workers, and neighborhood association leaders. The success of the activity is measured by assessing participants' knowledge before and after the education is conducted. After education was provided, there was an 84% improvement in participants' knowledge. This activity involved community leaders, so it is hoped that it can increase knowledge and understanding of the importance of P4K.